Probing the distribution of pharmaceutical compounds in cells using ToF-SIMS - Newman, Carla A.F. Fernandes (2019)
The primary objective of this thesis is to describe the work that I have undertaken during my PhD, evaluating the applicability of Time of Flight Secondary Ion Mass Spectrometry (ToF-SIMS) to study intracellular drug distribution. ToF-SIMS, as a technique has been widely used to characterize inorganic1 and organic materials, or even unexpected mixtures of both. My objective is to determine if that can be extended to drug discovery, by identifying pharmaceutical drugs in biological matrices such as cells. In drug discovery, intracellular drug distribution is a subject of profound interest, as scientists need to know if the drug is reaching the target of interest, or if is having adverse off-target activity. However, the techniques currently used to inform on this do not provide a definitive answer to the question, as either spatial resolution or molecular properties are compromised. For example, Matrix Assisted Laser Desorption Ionisation (MALDI) cannot achieve sub-cellular spatial resolution4 and even the most advance microscopy applications are dependent on labels that might compromise the physical-chemical properties of a drug molecule. ToF-SIMS bridges the gap, as it has improved spatial resolution and the drug molecules are presented to the in vitro or in vivo system label free with minimal sample preparation. SIMS is also capable of providing three-dimensional information and even potential metabolomics information when OrbiSIMS is employed3.In this study, I describe the first time a drug molecule, amiodarone, was visualized inside a mammalian cell using ToF-SIMS, this work was published in 2015. I then extend that methodology to other cell lines, and compare the ToF-SIMS data with Liquid-Chromatography tandem Mass Spectrometry data. This study also considers the variability found within cell populations and how different cells have a range of amiodarone intensities, and therefore exhibit different incorporation rates despite being derived from the same clones; this work was published in 2017. This thesis then focuses on the applicability of ToF-SIMS to the analysis of other drug molecules and investigates if a compound’s physical-chemical properties can provide any indication of the ionisation efficiency of a pharmaceutical drug in ToF-SIMS, this work is currently being written for a peer reviewed publication. The last chapter concentrates on bacterial imaging using both ToF and Orbi SIMS; the former allows the visualization of a drug molecule inside the bacteria of interest and the latter allows lower resolution imaging but extraction of metabolomic information as a result of the high mass resolution, high mass accuracy data generated by the Orbitrap mass analyser.